Rights as security : the theoretical basis of security of person - Powell, Rhonda Louise, 1979- (Oxford : Oxford University Press, 2019)
The right to security of person is widely recognized but little understood. Courts, legislatures, and scholars disagree about how the right to security of person should be defined. This text investigates the meaning of the right to security of person through an analysis of its constituent parts. Applying an original conceptual analysis of 'security', the right to security of person imposes both positive and negative duties. Also, identifying the interests to be protected by the right requires a theory of personhood or wellbeing such as Amartya Sen and Martha Nussbaum's 'capabilities approach'.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 13, 2019).
Keywords: Human security; Human rights